2010
DOI: 10.1007/s12666-010-0080-3
|View full text |Cite
|
Sign up to set email alerts
|

The effects of notch geometry on fatigue life using notch sensitivity factor

Abstract: The notch sensitivity of a material is a measure of how sensitive a material is to notches or geometric discontinuities. Notch sensitivity is influenced by many parameters such as notch geometry. Three types of notch geometries, V-shape, U-shape and -shape notches of various sizes are considered in this investigation. Two steel alloys of high and low strength (designated by HS-steel and LS-steel) are used in this work. Stress concentration is obtained by numerical simulation and the literature and fatigue redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…A comparison between the variations of yield stress versus notch length for brass and steel at the velocity of 5 mm s )1 is shown in Figure 23. It is interesting to note that the effect of v-notches on dynamic behaviour of materials examined in this work is quite similar to that observed by Majzoobi and Daemi [10] in their study of the effect of v-notches on fretting fatigue behaviour of the same materials. A typical result is shown in Figure 24.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…A comparison between the variations of yield stress versus notch length for brass and steel at the velocity of 5 mm s )1 is shown in Figure 23. It is interesting to note that the effect of v-notches on dynamic behaviour of materials examined in this work is quite similar to that observed by Majzoobi and Daemi [10] in their study of the effect of v-notches on fretting fatigue behaviour of the same materials. A typical result is shown in Figure 24.…”
Section: Resultssupporting
confidence: 87%
“…However, there is lack of information about K t for ‐shape notches. Majzoobi and Daemi [10] obtained K t for all notch geometries by numerical simulation using finite element method. They verified their results by those reported in the literature [8 & 9].…”
Section: Stress Concentrationmentioning
confidence: 99%
“…On the other hand, a notch induced HCF strength weakening is observed for some materials. For example, Haibach and Matschke et al and Majzoobi and Daemi observed that for structural steels, Karry and Dolan for brass, and Bennet and Weinberg for certain aluminium alloys.…”
Section: Introductionmentioning
confidence: 99%
“…If the components are subjected to cyclic loading for which the material cannot relieve such high stresses, they could suffer a sudden fracture that happens more promptly in comparison with unnotched structures. The presence of perforated holes or notches can reduce dramatically the fatigue life of components in some circumstances [4,5]. Many studies have dealt with the effect of holes of various shapes and dimensions on fatigue life of engineering components under cyclic loading [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of perforated holes or notches can reduce dramatically the fatigue life of components in some circumstances [4,5]. Many studies have dealt with the effect of holes of various shapes and dimensions on fatigue life of engineering components under cyclic loading [5,6]. In the case of cut-outs and holes, edge bluntness and rotation were recognized to be significant design variables and a number of works have dealt with these effects on composite plates [7,8].…”
Section: Introductionmentioning
confidence: 99%